INFORMATION RECYCLING MATHEMATICAL METHODS FOR PROTEAN SYSTEMS: A PATH-WAY APPROACH TO A GEOMETRIC PROGRAM - Kumar, S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: It is assumed that input values in a mathematical model may change frequently due to interactions that may be external or internal and/or may be due to design considerations. This changing environment is typical in a design situation where various possibilities are tried out before accepting one as the final design. Within the changing environment, a solution procedure has been described that attempts to obtain the solution to the changed problem by using the information and results already available from the solution of the problem that was obtained before changes occurred. The author in [15] has called this a